Pengaruh Promosi Melalui Sosial Media Dan Harga Terhadap Keputusan Pembelian Keripik Buah Merek Fiona - Sari, Juwita Permata; Rachma, N; Slamet, Afi Rachmat (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine "the influence of promotion through social media and price on purchasing decisions for Fiona brand fruit chips". This research uses quantitative research methods using a questionnaire with a 1-5 Likert scale. The population in this study were social media followers of Fiona brand fruit chips who had made purchases. The sampling method used was purposive sampling, with a total of 85 respondents. Data analysis was carried out using research instrument tests, classical assumption tests, multiple linear regression analysis tests, hypothesis tests and coefficient of determination tests. The collected data was analyzed using IBM SPSS Statistics software. The results of simultaneous testing of the influence of promotion through social media and price have a positive and significant influence on purchasing decisions. Partial test results show that promotion through social media and price influence purchasing decisions. Keywords: Social Media Promotion, Price, Purchase Decision